Land Use and Soil Resources - Braimoh, Ademola K.; Vlek, Paul L. G.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
Land-use change is one of the main drivers of many environmental change processes. It influences the basic resources of land use, including the soil. Its impact on soil often occurs so creepingly that land managers hardly contemplate initiating ameliorative or counterbalance measures. Poor land management has degraded vast amounts of land, reduced our ability to produce enough food, and is a major threat to rural livelihoods in many developing countries. To date, there has been no single unifying volume that addresses the multifaceted impacts of land use on soils. This book has responded to this challenge by bringing together renowned academics and policy experts to analyze the patterns, driving factors and proximate causes, and the socioeconomic impacts of soil degradation. Policy measures to prevent irreversible degradation and rehabilitate degraded soils are also identified.
Impact of Land Use on Soil Resources -- Soil Organic Carbon Dynamics and Land-Use Change -- Land-Use Change and Global Food Production -- Soil Erosion and Conservation in Global Agriculture -- Soil Erosion Studies in Northern Ethiopia -- Soil Degradation Under Irrigation -- Nutrient and Virtual Water Flows in Traded Agricultural Commodities -- The Lesson of Drente's (3z(BEssen(3y(B: Soil Nutrient Depletion in sub-Saharan Africa and Management Strategies for Soil Replenishment -- Soil Quality and Methods for its Assessment -- The Impact of Urbanization on Soils.s
Keywords: Earth sciences; Geobiology; Environmental sciences; Physical geography; Environment; Environmental management; Soil science; Soil conservation; Earth Sciences; Environmental Science and Engineering; Environment, general; Soil Science & Conservation; Environmental Management; Physical Geography; Biogeosciences; Electronic books